LEGAL EDUCATION AND SOCIAL JUSTICE: CONFRONTING PREJUDICE IN THE UNIVERSITY SPACE - Coelho, Antônio Carlos (Seven Editora, 2025)
This paper presents the results of a study that aimed to analyze the perception of the role of legal education among law students, based on the observation of tensions between the principles taught and the practices experienced in the academic environment. Using a qualitative approach and a bibliographical survey of authors in the field, it is evident that, despite legal discourse centered on dignity, equality, and ethics, everyday university life still reproduces forms of exclusion, prejudice, and silencing. Such contradictions compromise students’ critical thinking, undermine their well-being, and limit the development of a transformative legal culture. The conclusion is that there is an urgent need for institutional and pedagogical changes that align legal education with the principles of human rights education, promoting more inclusive and diversity-sensitive environments capable of training professionals committed to justice and the consolidation of a truly democratic society. DOI: https://doi.org/10.56238/sevened2025.040-008